Risk of Sarcopenia and Osteoporosis in Male Tuberculosis Survivors: Korea National Health and Nutrition Examination Survey. Issue 1 (December 2017) - Choi, Chang-Jin; Choi, Whan-Seok; Kim, Churl-Min; Lee, Sook-Young; Kim, Kyung-Soo
Abstract Short-term prospective studies have suggested that pulmonary tuberculosis (TB) preludes permanent loss of lean tissue and fat mass even when TB treatment is effective. The aim of this study was to estimate the risk of sarcopenia and osteoporosis among Korean male TB survivors. Data of the population-based, Korea National Health and Nutrition Examination Survey (KNHANES) (2008–2011) were analyzed, including 3, 228 males aged 50 years or older who underwent chest X-ray (CXR) and dual-energy x-ray absorptiometry (DEXA). TB survivors having both medical history and TB scars on CXR had increased risk of sarcopenia (odds ratio [OR] 3.44, 95% confidence interval [CI] 1.79–6.68) and osteoporosis (OR 1.75, 95% CI 1.04–2.95) after adjusting for age, height, smoking, alcohol, physical activity, serum 25-hydroxyvitamin D, parathyroid hormone level, education, and fat mass index. Having TB scars on CXR without medical history of TB was an independent risk factor of sarcopenia (OR 2.05, 95% CI 1.05–4.00), but not a risk factor of osteoporosis. Sarcopenia and low bone mineral density are prevalent in pulmonary TB survivors with TB scars on CXR. Medical history of TB with TB scars on CXR is an independent risk factor for sarcopenia and osteoporosis.